Importance of syngap1 syndrome diagnosis in autism spectrum disorder for dental treatment - ZINK,Adriana Gledys (2021)
ABSTRACT This paper reports on a patient with initial clinical diagnosis of Autism Spectrum Disorder level 3 and genetically confirmed as Syngap1 Syndrome (Synaptic RasGTPase activating protein). This study aimed to show the importance of genetic testing and accurate diagnoses associated with syndromes for the planning and accomplishment of dental treatments. The new diagnosis allowed reorganization of the plan and was useful in decision-making for the clinical practice of dental treatment for patients diagnosed with Syngap1.